2013
DOI: 10.1371/journal.pone.0055848
|View full text |Cite
|
Sign up to set email alerts
|

A Powerful Yeast Model to Investigate the Synergistic Interaction of α-Synuclein and Tau in Neurodegeneration

Abstract: Several studies revealed consistent overlap between synucleinopathies and tauopathies, demonstrating that α-synuclein (ASYN) and tau co-localize in neurofibrillary tangles and in Lewy bodies from Alzheimer’s and Parkinson’s disease patients and corresponding animal models. Additionally, it has been shown that ASYN can act as an initiator of tau aggregation and phosphorylation and that these two proteins directly interact. Despite these evidences, the cellular pathway implicated in this synergistic interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 76 publications
(89 reference statements)
3
38
0
1
Order By: Relevance
“…25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of p-Tau have also been observed in vivo in several toxin [16][17][18] and transgenic α-Syn models of PD, 19,20 suggesting that p-Tau may be an important common factor in the neurodegeneration of not only tauopathies but also of synucleinopathies, such as PD. [21][22][23][24] Most studies to date have focused on the formation and accumulation of Tau and p-Tau in idiopathic PD. Yet several studies have provided evidence that leucine-rich repeat kinase-2 (LRRK2), a kinase, that when mutated is involved in familial forms of PD, can directly interact with, and activate GSK-3β, resulting in increased p-TAU formation.…”
mentioning
confidence: 99%
“…Cell lysates were prepared as described (37). Briefly, cells were harvested by centrifugation, washed in double-distilled H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, it has been reported that co-expression with the gene encoding synuclein aggravates the toxic effects of overexpression of the latter [88]. More recently, co-expression of tau and α-synuclein genes from genetically stable single-copy yeast integrants confirmed the strong synergistic toxicity [89] which was attributed to the formation of inclusions of α-synuclein and of insoluble cytoplasmic tau aggregates.…”
Section: Tau Expression In Saccharomyces Cerevisiae and Merits Of Klumentioning
confidence: 99%